Upaya meningkatkan kualitas proses pembelajaran dan media pembelajaran matematika bagi masyarakat calon guru profesional dalam program PKM - Hisyam Ihsan; Bernard Bernard; Ahmad Zaki (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The PKM program is carried out with the method of providing training and mentoring to participants regarding the development of learning media/mathematical teaching aids to improve the quality of the learning process with the aim of (1) to increase knowledge about the development of mathematics learning media/mathematical teaching aids, (2) participants can implement with both the development of mathematics learning media/mathematical teaching aids in the learning process, and (3) participants can disseminate or disseminate knowledge about developing mathematics learning media/mathematical teaching aids. The main target audience for the PKM Program activities are school supervisors, school principals and school teachers in Tinggimoncong sub-district, Gowa district, South Sulawesi province. The results obtained in PKM program activities are increased knowledge and concept of developing mathematics learning media/mathematical teaching aids of PKM program participants, increasing skills in developing mathematics learning media/mathematical teaching aids of PKM program participants, PKM program participants can make examples and arrange learning media development activities mathematics/mathematics teaching aids in learning classes, and PKM program participants can implement the development of mathematics learning media/mathematics teaching aids in learning in schools. Other results obtained were increased motivation of participants in knowing the material for developing mathematics learning media/mathematical teaching aids and the high enthusiasm of participants in disseminating or disseminating the results of the PKM program, especially material for developing mathematics learning media/mathematical teaching aids. Outputs of PKM activities are (1) increasing participant's knowledge regarding activity materials, (2) scientific articles published at national seminars, and (3) publications on PKM implementation on online media.